Fracture behavior of diamond-like carbon films on stainless steel under a micro-tensile test condition - Choi, HW; Lee, KR; Wang, RZ; Oh, KH (ELSEVIER SCIENCE SA, 2006)
We investigated the stability of the DLC film coated on 304 stainless steel substrate by r.f. PACVD method. Fracture and spallation behaviors of the coating were observed during micro-tensile test of the film/substrate composite. As the tensile deformation proceeded, the cracks of the film appeared in the perpendicular direction to the tensile axis. Further deformation resulting in the local necking with shear band of 55 degrees inclined to the tensile axis, induced the spallation of the film, which was initiated at the cracks of the film, and was aligned along the slip directions. We found that both the cracking and the spallation behaviors are strongly dependent on the pretreatment condition, such as Ar plasma pretreatment or Si buffer layer deposition. The spallation of the film was significantly suppressed in an optimized condition of the substrate cleaning by Ar glow discharge. These results show that the spallation behavior during the tensile test can be used to estimate the interfacial strength of the coating with relatively poor adhesion. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: BIOLOGICAL APPLICATIONS; MECHANICAL-PROPERTIES; SUBSTRATE; COATINGS; CRACKING; INTERFACE